2008
DOI: 10.1529/biophysj.108.133884
|View full text |Cite
|
Sign up to set email alerts
|

Taxol Allosterically Alters the Dynamics of the Tubulin Dimer and Increases the Flexibility of Microtubules

Abstract: Taxol is a commonly used antitumor agent that hyperstabilizes microtubules and prevents cell division. The interaction of Taxol with tubulin and the microtubule has been studied through a wide array of experimental techniques; however, the exact molecular mechanism by which Taxol stabilizes microtubules has remained elusive. In this study, through the use of large-scale molecular simulations, we show that Taxol affects the interactions between the M and H1-S2 loops of adjacent tubulin dimers leading to more st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
106
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(115 citation statements)
references
References 41 publications
7
106
1
1
Order By: Relevance
“…Based on a molecular dynamics simulation of a small section of six tubulin monomers [13], we show that the observed fluctuations of this section are consistent with linear elastic constants for both bending and stretching along the microtubule axis.…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…Based on a molecular dynamics simulation of a small section of six tubulin monomers [13], we show that the observed fluctuations of this section are consistent with linear elastic constants for both bending and stretching along the microtubule axis.…”
mentioning
confidence: 60%
“…Most often mechanical properties are elucidated in experiments by calculating a forcedisplacement curve as the system is subjected to an applied force. Our simulations were performed as equilibrium molecular dynamics simulations [13] and did not include such a force; however, we can make use of the equipartition theorem and knowledge of the energy involved in the bending, compression or shear of a sheet, assuming a harmonic dependence. In the case of bending, the elastic energy can be described by the bending rigidity of an elastic shell formed by the protofilaments, according to…”
Section: H Y S I C a L R E V I E W L E T T E R S Week Ending 8 Januarmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular dynamics simulations on tubulin hexamer were used to study the effects of taxol, a natural microtubule-stabilizing agent. It was suggested that taxol increases b-tubulin flexibility at regions that surround the bound nucleotide and allows the microtubule to counteract the conformational changes induced by nucleotide hydrolysis [30]. More recently, molecular dynamics simulations performed on linear ab-tubulin hexamers brought new arguments to the ''lattice model''.…”
Section: Introductionmentioning
confidence: 99%
“…For this analysis we applied the protocol described in the work by Mitra et al 29 We first determined the number of independent conformations in our MD trajectories by calculating the autocorrelation function of Root Mean Square Deviation (RMSD) of the structures. We found a correlation time of 2.5 ns, corresponding to 10 independent structures in each of our 25 ns trajectories.…”
mentioning
confidence: 99%